Feeding the ancient Greek city (Leuven ; Paris ; Dudley, Mass.)
xi, 207 sayfa
Keywords: “In ancient cities, 'daily bread' was a subject of prayer. Grain-harvests could be fickle, but a regular supply was a matter of survival. Food-shortage could lead to social unrest, and long-term solutions required all kinds of political an institutional resources from the authorities. Yet feeding the city was not just a problem. It was an opportunity for the political management of the poor, for competitive display among the elite, and for making money. The essays in this volume present cities and societies which responded to these challenges in very different ways, from the agro-towns in which the citizens commuted to their fields to the market-supplied towns in which an urban proletariat worked for their bread. The articles debate the food supply through all its aspects, economic, demographic, political and institutional to give a new perspective on this debate at the heart of our understandings of ancient society.” --